Problems About Methods of Teaching Vocabulary at the Non-Philological Universities (Journal of Pedagogical Inventions and Practices, 2022)
This article deals with the problem of finding new techniques and ways to increase motivation for learning new vocabulary in the English teaching. According to the author, one of these forms are methods, the introduction of which contribute to the effective learning of the vocabulary. As the points out working with vocabulary is an important part of any English lesson, and vocabulary itself requires a separate approach in teaching. The author highlights the main problems in this sphere.